Effects of modified constraint-induced movement therapy on reach-to-grasp movements and functional performance after chronic stroke: a randomized controlled study - Lin, K.-C.; Wu, C.-Y.; Wei, T.-H.; Gung, Chang; Lee, C.-Y.; Liu, J.-S. (Clinical rehabilitation, 2007)
Objective: To evaluate changes in (1) motor control characteristics of the hemiparetic hand during the performance of a functional reach-to-grasp task and (2) functional performance of daily activities in patients with stroke treated with modified constraint-induced movement therapy. Design: Two-group randomized controlled trial with pretreatment and posttreatment measures. Setting: Rehabilitation clinics. Subjects: Thirty-two chronic stroke patients (21 men, 11 women; mean age=57.9 years, range=43—81 years) 13—26 months (mean 16.3 months) after onset of a first-ever cerebrovascular accident. Intervention: Thirty-two patients were randomized to receive modified constraint-induced movement therapy (restraint of the unaffected limb combined with intensive training of the affected limb) or traditional rehabilitation for three weeks. Main measures: Kinematic analysis was used to assess motor control characteristics as patients reached to grasp a beverage can. Functional outcomes were evaluated using the Motor Activity Log and Functional Independence Measure. Results: There were moderate and significant effects of modified constraint-induced movement therapy on some aspects of motor control of reach-to-grasp and on functional ability. The modified constraint-induced movement therapy group preplanned reaching and grasping (P=0.018) more efficiently and depended more on the feedforward control of reaching (P=0.046) than did the traditional rehabilitation group. The modified constraint-induced movement therapy group also showed significantly improved functional performance on the Motor Activity Log (P<0.0001) and the Functional Independence Measure (P=0.016). Conclusions: In addition to improving functional use of the affected arm and daily functioning, modified constraint-induced movement therapy improved motor control strategy during goal-directed reaching, a possible mechanism for the improved movement performance of stroke patients undergoing this therapy.